2016
DOI: 10.1051/0004-6361/201628547
|View full text |Cite
|
Sign up to set email alerts
|

A distinct magnetic property of the inner penumbral boundary

Abstract: Context. We recently presented evidence that stable umbra-penumbra boundaries are characterised by a distinct canonical value of the vertical component of the magnetic field, B stable ver . In order to trigger the formation of a penumbra, large inclinations in the magnetic field are necessary. In sunspots, the penumbra develops and establishes by colonising both umbral areas and granulation, that is, penumbral magneto-convection takes over in umbral regions with B ver < B stable ver , as well as in granular co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
5
25
0
3
Order By: Relevance
“…In our case, we do not have enough information on the magnetic field configuration in the pore during the formation process of the anomalous penumbra due to the lack of SP scans during those stages. Nonetheless, its evolution on the G-band images looks in some aspects similar to the case studied in Jurčak et al (2017): the filaments seem to grow at the expense of the adjacent pore. However, an important difference is that in the case studied by Jurčak et al (2017), the penumbra ends up as an orphan penumbra once the pore has disappeared, i. e. the filaments are not connected to any umbral region, while the anomalous penumbra in our study is continually attached to the umbra of the main sunspot.…”
Section: Discussionsupporting
confidence: 52%
“…In our case, we do not have enough information on the magnetic field configuration in the pore during the formation process of the anomalous penumbra due to the lack of SP scans during those stages. Nonetheless, its evolution on the G-band images looks in some aspects similar to the case studied in Jurčak et al (2017): the filaments seem to grow at the expense of the adjacent pore. However, an important difference is that in the case studied by Jurčak et al (2017), the penumbra ends up as an orphan penumbra once the pore has disappeared, i. e. the filaments are not connected to any umbral region, while the anomalous penumbra in our study is continually attached to the umbra of the main sunspot.…”
Section: Discussionsupporting
confidence: 52%
“…Based on a study of ten sunspots, Jurčák (2011) concluded that the inner penumbral boundaries are defined by the critical value of the vertical component of the magnetic field, i.e., B stable = 1.8 kG. Recently, Jurčák et al (2017) studied penumbra formation around a pore, which supports the scenario earlier proposed by Jurčák (2011) and Jurčák et al (2015), i.e., the stable vertical component of magnetic field is needed to establish the umbra-penumbra boundary.…”
Section: Introductionsupporting
confidence: 56%
“…If the vertical component of magnetic field (B ver ) in pore was smaller than B ver stable , the penumbral magneto-convective mode in the pore would be not hindered and a stable pore-penumbra boundary would not be established. Jurčák et al (2017) further analyzed the penumbral formation of a pore and confirmed the necessity of B ver stable for establishing a stable umbra-penumbra boundary (Jurčák et al 2015). They found that the penumbra grew at the expense of magnetic flux of the pore, which supports the result proposed earlier by Watanabe et al (2014).…”
Section: Introductionsupporting
confidence: 73%